Overview of Emotion Regulation in Working Mothers Who Experience Dual Role Conflict - Pradani, Zalza Putri; Widyastuti, Widyastuti (Advances in Cancer Science, 2024)
The purpose of this study is to characterize the emotional regulation of working women who deal with dual role conflict, or conflicts between work at home and job outside the home. This study aims to identify the variables influencing the emotional regulation of working mothers who encounter dual role conflict as well as to give an overview of the emotional regulation practices of these mothers. The issue where mothers experience a dual role conflict between working and being a housewife is the focus of the researcher's qualitative technique. Three working mothers who had also transitioned to being housewives with children and significant others or informants made up the total number of respondents in this study. Formal interviews were used to gather data. The findings demonstrated that each of the three respondents was able to discuss several facets of emotional regulation, such as reaction modulation, attention deployment, situation alteration, and situation selection. While gender, cognitive ability, and social support are determinants in emotion regulation.